Exploring the Effects of Nitrogen Fertilization Management and Soil Factors on the Yield and Quality of Flue-Cured Tobacco in China—A Quantitative Research - Huan, Weiwei; Irfan, Muhammad; Yokamo, Solomon; Lu, Hailong; Lu, Dianjun; Chen, Xiaoqin; Wang, Huoyan; Zhou, Jianmin (Agronomy (Basel), 2024)
Tobacco, a pivotal economic crop in China, faces the challenge of securing high-quality raw materials for its industry due to unbalanced and inefficient nitrogen (N) application. To assess the impact of fertilizer management and soil factors on the yield and quality of flue-cured tobacco (FCT), a meta-analysis was conducted across 82 peer-reviewed research studies. The findings demonstrated that both fertilizer management and soil properties exerted a significantly greater influence on yield (63.13% and 62.05%, respectively) than the proportion of superior and medium tobacco (PSMT) (23.57% and 23.83%, respectively). Multiple models were conducted to analyze the N application rate for maximum yield and PSMT, respectively, resulting in an optimum range from 90 to 100 kg N ha−1. The highest yield and PSMT increments were observed with fertilizer timing (FT) applied twice, a basal fertilizer ratio (BFR) exceeding 50%, and a soil pH below 6.5. The nicotine content escalated with increasing N application rates (NR) and soil nitrogen content, peaking at NR over 120 kg N ha−1 and soil total nitrogen (TN) above 2 g kg−1. Stepwise regression modeling indicated that nicotine content was positively influenced by fertilizer management factors (including NR, fertilizer timing, and BFR), as well as initial soil nitrogen content (AN and TN). However, it was negatively correlated with available potassium (AK). Therefore, the results of this meta-analysis suggest that effective fertilizer management, slightly acidic soils enriched with AK, and lower N supply capacity are crucial for enhancing leaf quality while reducing nicotine content. This approach promises improved economic and environmental returns for the tobacco industry in China.